Diagnostic value of rEBUS-TBLB combined distance measurement method based on ultrasound images in bronchoscopy for peripheral lung lesions - Shuhong Guan; Xiaoli Xu; Xiaoqin Zhu; Yunqi Ge; Jun Xie; Jun Zhou (SLAS Technology)
Traditional imaging methods have limitations in the diagnosis of peripheral lung lesions. The aim of this study is to evaluate the diagnostic value of the distance measurement method based on ultrasound image-based inverted electrostrain (rEBUS) combined with thoracoscopic lung biopsy (TBLB) for peripheral lung lesions. A group of patients with peripheral lung lesions were recruited for the study, and rEBUS examination was performed simultaneously during TBLB. Using rEBUS ultrasound images combined with electrostrain information, evaluate the morphological characteristics of peripheral lung lesions and the elastic properties of internal tissues. By comparing with pathological examination results, both rEBUS-D-TBLB and rEBUS-GS-TBLB have a higher positive diagnostic rate for PPL under bronchoscopy. However, rEBUS-D-TBLB is more effective in diagnosing benign PPL with ≥ 3 cm PPL than rEBUS-GS-TBLB. The rEBUS-TBLB combined ranging method has shown high accuracy and sensitivity in diagnosing peripheral lung lesions. Ultrasound images provide clear morphological features of the tumor, while the electrical strain information of rEBUS provides elastic information of the internal tissue of the tumor, further improving the accuracy of diagnosis.